Social Norms Influencing the Performance of the Youth Owned Small Micro-Enterprises in Mihuu Ward, Bungoma County, Kenya - Anthony, Dr Alexis; Mulongo, Mikisi Wycliffe; Simotwo, Peter (IJRDO- Journal of Educational Research, 2021)
An entrepreneur is a person who is always looking for change, responds to change, and exploits it as an opportunity. With adequate requirement of capital, education facility and own creativity, intelligence, energetic youth can be turned into decent business people. The problem in this study is the high level of poverty amongst the youth who seem to be idle and not earning for themselves but simply being senior dependants on the few in the society who appear to be doing well. This study has both theoretical and practical implications for the future of Small Micro Enterprises in Kenya. The study used mainly the knowledge Spill over theory and the traits theory. The dependent variable is business performance while the independent one is cultural factors. The design of the study was descriptive and used mixed methodology because it involved both quantitative and qualitative techniques. The location of the study was in Mihuu ward in Bungoma County with a target population of 32 youth groups with a census of the entire study groups. The data collection instrument was questionnaires and interviews and pretesting of the questionnaire was done in one of the market centres within the study population. The researcher considered the analysis phase right from the beginning because the kind of data obtained can affect the choice of analysis procedures. In planning for research, the researcher intends to keep in mind the link between questions intended to provide the research answer, the data and their analysis. For the quantitative data, the researcher used SPSS technique in analyzing the data descriptively collected. The findings showed that the cultural values and practices have a significant impact in determining the performance of these enterprises by influencing the group formation, bonding, cohesiveness and goal achievement. These tenets of the culture are thus able to inculcate entrepreneurial traits into the members of the community. The study concludes by saying that cultural factors have a significant impact on the performance of youth – owned enterprises in Mihuu Ward, Bungoma County. The study recommends that the YEDF considers the social – cultural factors as important determinants in promoting the use of YEDF.